Optical free-carrier generation in silicon nano-waveguides at 1550 nm - Gil-Molina, Andres; Aldaya, Ivan [UNESP]; Pita, Julián L.; Gabrielli, Lucas H.; Fragnito, Hugo L.; Dainese, Paulo (AIP Publishing, 2018)
We report on time-resolved pump and probe characterization of linear and nonlinear optical generation of free carriers in a silicon strip nano-waveguide at the 1550 nm communication band. Analytical expressions were developed to extract the carrier density averaged along the waveguide length from the measured free-carrier absorption for different input pump power levels. This allows us to discriminate the contributions from two-photon absorption (TPA) and single-photon absorption (SPA), obtaining TPA and SPA coefficients of (1.5 ± 0.1) cm/GW and (1.9 ± 0.1) m-1, respectively. Our results reveal that the effective TPA within the waveguide is higher than the value reported for bulk silicon. In addition, we find that for the waveguide under test, the carrier generation via SPA plays an important role up to ∼300 mW, and therefore, it must be taken into account to correctly assess free-carrier effects in silicon photonic devices.